Arterial Resection for Pancreatic Cancer: Feasibility and Current Standing in a High-Volume Center - Lei Ren, MD; Carsten Jäger, MPH; Stephan Schorn; Ilaria Pergolini; Rüdiger Göß; Okan Safak; Maximilian Kießler; Marc E. Martignoni; Alexander R. Novotny; Helmut Friess; Güralp O. Ceyhan; Ihsan Ekin Demir (Annals of Surgery Open, 2023)
Background:. Arterial resection (AR) during pancreatectomy for curative R0 resection of pancreatic ductal adenocarcinoma (PDAC) remains a controversial procedure with high morbidity. Objective:. To investigate the feasibility and oncological outcomes of pancreatectomy combined with AR at a high-volume center for pancreatic surgery. Methods:. We retrospectively analyzed our experience in PDAC patients, who underwent pancreatic resection with AR and/or venous resection (VR) between 2007 and 2021. Results:. In total 259 PDAC patients with borderline resectable (n = 138) or locally advanced (n = 121) PDAC underwent vascular resection during tumor resection. From these, 23 patients had AR (n = 4 due to intraoperative injury, n = 19 due to suspected arterial infiltration). However, 12 out of 23 patients (52.2%) underwent simultaneous VR including 1 case with intraoperative arterial injury. In comparison, 11 patients (47.8%) underwent AR only including 3 intraoperative arterial injury patients. Although the operation time and bleeding rate of patients with AR were respectively longer and higher than in VR, no significant difference was detected in postoperative complications between VR and AR (P = 0.11). The final histopathological findings of PDAC patients were similar, including M stage, regional lymph node metastases, and R0 margin resection. The mortality of the entire cohort was 6.2% (16/259), with a tendency to increase mortality in the AR cohort, yet without statistical significance (VR: 5% vs AR: 21.1%; P = 0.05). Although 19 (82.6%) patients had PDAC in the final histopathology, only 6 were confirmed to have infiltrated arteria. The microscopic distribution of PDAC in these infiltrated arterial walls on hematoxylin-eosin staining was classified into 3 patterns. Strikingly, the perivascular nerves frequently exhibited perineural invasion. Conclusions:. AR can be performed in high-volume centers for pancreatic surgery with an acceptable morbidity, which is comparable to that of VR. However, the likelihood of arterial infiltration seems to be rather overestimated, and as such, AR might be avoidable or replaced by less invasive techniques such as divestment during PDAC surgery.